The impact of formal decision processes on e-Government projects - Leif Sundberg; Aron Larsson (Administrative Sciences, 2017)
This paper studies associations between the use of formal decision-making processes in e-Government projects and the outcomes of these projects. By doing so, this study contributes to the decision sciences as well as to the fields of e-Government, information systems and public administration. Data were collected using a survey conducted among Swedish national government agencies and municipalities. Variables that have been investigated are the defining and weighting of objectives, resource allocation and assessment of whether objectives are met, as well as to what extent risk analysis was conducted. The results reveal that successful projects distinguish themselves by involving more activities related to formal decision-making procedures, especially with respect to stakeholder inclusion and weighting of objectives. These initiatives also manage more types of risks, including organizational issues. Future research should continue to explore the possible benefits of formal decision-making and risk analysis in e-Government.
Keywords: 350; e-Government; decision-making; decision theory; public values; risk analysis; information systems; public management; public administration